2016
DOI: 10.5513/jcea01/17.2.1708
|View full text |Cite
|
Sign up to set email alerts
|

The uptake and release of humidity by wool irradiated with electron beam

Abstract: In this work, wool samples a) degreased and stored in desiccator (WD), b) degreased and stored freely (WF), c) cleaned in water and stored freely (WW) were irradiated by accelerated electron beam with doses within the range (0-400) kGy in air. Content of S-sulphonate as primary oxidation product was determined in WD using FTIR spectra inverted in the second-order derivative spectra. The uptake of humidity by all the samples at room temperature and 97% relative humidity was examined gravimetrically. As expected… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 11 publications
(15 reference statements)
0
3
0
Order By: Relevance
“…Being the generated species of polar character, the correspondent surface energy of the fibres should grow. This parameter was really determined in the degreased and water scoured wool samples [28]. It was found that the surface energy increased immediately already after the lowest dose and became stable from 100 kGy despite the fact that the content of polar groups continued to increase in the bulk.…”
Section: Ftir and Raman Spectralmentioning
confidence: 99%
“…Being the generated species of polar character, the correspondent surface energy of the fibres should grow. This parameter was really determined in the degreased and water scoured wool samples [28]. It was found that the surface energy increased immediately already after the lowest dose and became stable from 100 kGy despite the fact that the content of polar groups continued to increase in the bulk.…”
Section: Ftir and Raman Spectralmentioning
confidence: 99%
“…The precipitous deviation of wool moisture from an equilibrium value disrupts the original hydrogen bonds, which must also effect conformational changes in the secondary structure (α-helical, β-sheet, mixed, amorphous structure). Given that there is dual moisture in wool, bound physically and chemically, the process of uptake/release of water runs at a different rate [ 33 ]. In the case of dehydrated wool, recovery of the initial inter- and intramolecular bonds between water and keratin within the following, keeping in conventional laboratory conditions, requires some time.…”
Section: Resultsmentioning
confidence: 99%
“…Then, new polar functional groups formed by the electron beam effect, but also present without it, can interact with H 2 O more easily. Hanzlíková et al [ 33 ] reported an important increase in the surface energy of electron-irradiated wool. Because the number of new functional groups increases with rising dose, the amount of active sorption sites in the wool increases and rises with time, too.…”
Section: Resultsmentioning
confidence: 99%